Overview of the digital-to-analog converter module based on the MCP4725 chip and the digital-to-analog converter module based on the integrating RC circuit - Kirill A. Volobuev; Igor V. Trubin; Vitaly G. Trubin (Известия Томского политехнического университета: Промышленная кибернетика, 2024)
In technical cybernetic systems, it is impossible to do without exchanging information between devices. Most modern control devices are digital, but it is not uncommon for an analog signal to be required to control executive devices, which can be changed in a certain range. To receive an analog signal from a digital one, a special device is used – digital-to-analog converter. This article provides brief information about the types of signals and their differences. Two widely used digital-to-analog conversion modules are considered. They can be used to convert a digital signal from a microcontroller into an analog control signal of 0–10 V. The modules are controlled using the "Blue Pill" debugging board based on the STM32F103 microcontroller. The digital-to-analog converter module on the MCP4725 chip is controlled via the I2C interface. Another module based on the RC circuit converts the PWM signal from the microcontroller into an analog signal of 0–10 V. The article will be useful for students, engineers, and graduate students who want to study the operation of a PWM-based digital-to-analog converter and RC circuit, as well as connecting devices via the I2C interface.